A new species of Dimeria (Poaceae) from Andaman and Nicobar Islands, India - Gosavi, K.v.c.; Kamble, M.y.; Chandore, A.n.; Yadav, S.r. (Phytotaxa, 2016)
Dimeria andamanica (Poaceae) is herein described and illustrated as a new species. It is known from relict region of Chidiya Tapu, South Andaman of the Andaman Islands, India. The new species belongs to the Dimeria sect. Loriformes and is closely related to D. fischeri, but differs by the characters of raceme-rachis 1.5–2 mm wide, spikelets 6–7 mm long, lower glume 5–5.5 mm long, upper glume 5–6 mm long, lower lemma 3.5–4 mm long, upper lemma 4–5 mm long, upper floret palea present and anthers 1.5–2 mm long.